Role of NADPH Oxidase and GSH in Cystic Fibrosis - พงศ์นิมิตประเสริฐ นุชจิรา (Thai Bulletin of Pharmaceutical Sciences, 2015)
Cystic fibrosis (CF),an autosomal recessive disorder that is resulted from mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, leading to a reduction in apical membrane chloride transport. the mechannism of CF has been the subject of debate that it may be associated with nicotinamide adenine dinucle yide phosphate (์NADPH) oxidases and depletion of glutathione (GSH). NADPH oxidases are protein that tranfer electrons across biological membrane, resulting in the reactine oxygen specices (ROS) production and play a key role in host defenses in CF. Depletion of GSH in CF transport,and then contributes to an imbalance in the antioxidant defense and results in oxidatine stress. These effect can make cell damage from ROS